2021
DOI: 10.3389/fcvm.2021.644035
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Triglyceride-Glucose Index and Hypertension: A Meta-Analysis

Abstract: Background: Triglyceride-glucose (TyG) index is a recently proposed surrogate indicator of insulin resistance. Previous studies evaluating the association between TyG index and hypertension risk in general adult population showed inconsistent results. We performed a meta-analysis to systematically evaluate this association.Methods: Observational studies, which evaluated the independent association between TyG index and hypertension in the general adult population, were identified by systematic search of PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 31 publications
6
69
2
Order By: Relevance
“…Third, IR increases blood coagulability by promoting the activation, adhesion, and aggregation of platelet [29][30][31], while the unstable plaques and impaired vascular autonomic regulation caused by arteriosclerosis increase the chance of thrombosis. Fourth, Studies also reported that the TyG index was involved in the onset and development of hypertension [32], diabetes [6], and hyperuricemia [33], while stroke is often the combined effect of these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Third, IR increases blood coagulability by promoting the activation, adhesion, and aggregation of platelet [29][30][31], while the unstable plaques and impaired vascular autonomic regulation caused by arteriosclerosis increase the chance of thrombosis. Fourth, Studies also reported that the TyG index was involved in the onset and development of hypertension [32], diabetes [6], and hyperuricemia [33], while stroke is often the combined effect of these risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors have been associated with poor clinical outcomes in patients with acute IS. Moreover, a higher TyG index has been related to many risk factors of IS, such as hypertension [35] ▶table 2 Quality evaluation of the included cohort studies via the NOS. and diabetes [36], which may also partly explain the relationship between TyG index and poor prognosis in the patients with acute IS.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors have been associated with poor clinical outcomes in patients with acute IS. Moreover, a higher TyG index has been related to many risk factors of IS, such as hypertension 35 and diabetes 36 , which may also partly explain the relationship between TyG index and poor prognosis in the patients with acute IS. However, these may not be the predominant mechanisms because multivariate analyses with adjustment of the comorbidities were applied in all of the included studies when the association between TyG index and outcomes of patients with acute IS was presented.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were identified via systematic search of electronic databases of PubMed and Embase via the following terms: (1) “breakfast” OR “morning meal” OR “eating patterns” OR “meal frequency” OR “skipping meals” and (2) “hypertension” OR “blood pressure” OR “hypertensive.” The search strategies were developed based on previous meta-analyses of “skipping breakfast” [ 8 ] and “hypertension” [ 25 ], respectively, which have been validated in these previous meta-analyses. The search was limited to human studies published in English.…”
Section: Methodsmentioning
confidence: 99%